Unraveling the Man: Toxic Masculinity and Cowboy Culture in ‘The Power of the Dog' - Ardi Nugroho; Wandi Wijaya (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
This research explored how language, dialogue, and character portrayal in Jane Campion's 2021 film